Factors Influencing The Incidence of Gestational Hypertension in Sally Clinic, Tembung District, Deli Serdang Regency, North Sumatera Province, 2024 - Melisa Elisabeth Sinaga; Mesrida Simarmata; Srininta Srininta (OBAT: Jurnal Riset Ilmu Farmasi dan Kesehatan, 2025)
Hypertension in pregnancy is a dangerous condition in pregnancy because it can disturb the health of the mother and baby. Pregnancy Hypertension or Gestational Hypertension is a condition of systolic blood pressure of 140 mmHg and diastolic 90 mmHg or blood pressure increases by 30 mmHg or more and diastolic increases by 15 mmHg or more. Objective : To determine the factors that influence the incidence of gestational hypertension at the Sally Clinic in 2024. Population and Sample: Pregnant women who came to the Sally clinic experienced hypertension, the number of 30 people with a total population sampling technique, so the number of samples was 30 people. Place and time: at the Sally Clinic, Tembung on month April– July 2024. Results : Univariate : The majority of respondents with high school education were 15 people (50%), the majority had a good lifestyle were 18 people (60%), the majority had genetics were 26 people (87%), the majority were aged 20-35 years were 25 people (83%). The majority did not experience gestational hypertension as many as 21 people (70%). Bivariate : From 12 respondents with unhealthy lifestyles, 9 experienced gestational hypertension (30%). The results of the p value calculation = 0.000 , from respondents who had a family history of hypertension, 6 people overall experienced gestational hypertension, the P Value value = 0.000 <0.05 was obtained , the age of 9 respondents experiencing gestational diabetes, there were 5 respondents (17%) aged over 35 years, The results of the statistical analysis of the three variables showed a p-value <0.05, so Ha was accepted, namely there was a lifestyle and medical history, age with the incidence of gestational hypertension at the Sally Tembung Clinic in 2024. Conclusion : there is a relationship between lifestyle, medical history and age with the incidence of gestational hypertension at the Sally Tembung Clinic in 2024.